Impacts of low phytoplankton NO3−:PO43− utilization ratios over the Chukchi Shelf, Arctic Ocean. (August 2015) - Mills, Matthew M.; Brown, Zachary W.; Lowry, Kate E.; van Dijken, Gert L.; Becker, Susan; Pal, Sharmila; Benitez-Nelson, Claudia R.; Downer, Meryssa M.; Strong, Aaron L.; Swift, James H.; Pickart, Robert S.; Arrigo, Kevin R.
Abstract: The impact of Arctic denitrification is seen in the extremely low values for the geochemical tracer of microbial nitrogen (N) cycle source/sink processes N ⁎ ⁎ (Mordy et al. 2010). The utility of N ⁎ ⁎ as an oceanic tracer of microbial N cycle processes, however, relies on the assumption that phytoplankton utilize dissolved N and P in Redfield proportions, and thus changes in N ⁎ ⁎ are due to either N2 -fixation or denitrification. We present results from two cruises to the Chukchi Sea that quantify nutrient drawdown, nutrient deficits, and particulate nutrient concentrations to estimate production over the Chukchi Shelf and document lower than Redfield N:P utilization ratios by phytoplankton. These low ratios are used to calculate N ⁎ ⁎ (assuming a Redfield NO3 − :PO4 3− utilization ratio) and N N R ⁎ ⁎ (using the measured particulate N:P ratios) and, combined with current flow speed and direction measurements, to diagnose denitrification rates on the Chukchi Shelf. Our estimates of denitrification rates are up to 40% higher when Redfield proportions are used. However, the denitrification rates we calculate using N N R ⁎ ⁎ are still higher than previous estimates (up to 8 fold) of denitrification on the Chukchi shelf. These estimates suggest that Arctic shelves may be a greater sink of oceanic N than previously thought.